The war after next is here – what does the elephant look like?. Issue 4 (1st October 2016) - Shabtai, Shay
ABSTRACT: A comprehensive paradigm of future wars can be defined, and is called in this article "Extended conflicts." These can be characterized by strategic attrition, to which all national resources and all possible international legitimacy are mobilized, in order to achieve a resolution by transformation of the opponent. The use of military force in this kind of conflict is limited. The understanding that we are facing an era of extended conflicts will improve the way it is utilized.